Voices from the Field: Multiple Perspectives on a Co-Teaching in Student Teaching Model - Bacharach, Nancy; Heck, Teresa Washut (Educational (Re)naissance, 2012)
Teacher preparation programs face continued scrutiny and to address these concerns it is imperative that teacher educators examine all aspects of their current preparation programs. The student teaching experience is a critical component in teacher preparation, and must undergo careful review. The SCSU co-teaching model provides a proven alternative to the traditional student teaching experience. This model not only strengthens university/school partnerships, but also has the ability to provide benefits for all stakeholders.